Electrospun nanofibrous composites to control drug release and interaction between hydrophilic drug and hydrophobic blended polymer matrix - Haroosh, Hazim; Dong, Yu (Canadian Association for Composite Structures and Materials, 2013)
This study has developed new electrospun hybrid nanocomposite systems using poly(lactic acid) PLA: poly(ε-caprolactone) PCL blends and PLA: PCL / halloysite nanotubes-3-aminopropyltriethoxysilane (HNT-ASP) to take the advantage of the sustained release of hydrophilic drug tetracycline hydrochloride (TCH) from hydrophobic PLA: PCL composite system. The impact of interaction between the two typical drugs, namely TCH and Indomethacin (IMC), and PLA: PCL blends on the drug release was examined. The study also investigated the drug release kinetics by fitting the experimental release data with five mathematical models for drug delivery. The average nanofiber diameters were found to be significantly reduced when increasing the TCH concentration due to the enhancement of solution electrical conductivity in contrast to the presence of IMC. The addition of both TCH and IMC drugs to PLA: PCL blends reduce the crystallinity level, glass transition temperature Tg and melting temperature Tm values of PCL within the blends. The reduction of drug release and elimination of the impairment of the interaction between the polymer and drug were achieved by mobilizing TCH into HNT-ASP to be then embedded in the PLA: PCL nanofibers. The typical characteristic was clearly revealed with excellent agreement between obtained experimental data and Ritger-peppas and Zeng models in drug release kinetics.